Milk production, fluid balance and temperature regulation in lactating camels (camellus dromedarius). - Bekele, T. (Swedish University of Agricultural Sciences, 2010)
The aims of this thesis were to identify good milking and watering routines for camels, and to better understand the physiological mechanisms that enable camels to produce milk during long periods of water deprivation. Milk production was increased by changing the number of milkings from one to four times per day in an on-farm study. Camels that calved in the long dry season had a higher lactation yield than those that calved in the wet season. Seven camels were subjected to four watering regimes, each 16 days long with 5 days of daily watering in between. The regimes were: water offered once every day (W1); offered on days 4, 8, 12 and 16 (W4); on days 8 and 16 (W8) or on day 16 (W16). Milk yield decreased after about 8 days of water deprivation, and changes in milk fat, lactose and protein concentrations remained small during W16. Contrary to widespread belief, dehydrated camels did not dilute their milk, instead milk and blood plasma osmolality increased in parallel. Camels saved water by storing heat during daytime allowing body temperature to increase, and dissipating the heat during the cool night. Afternoon body temperature was around 39.0°C in all treatments but fell by 3 to 6°C at night, with the lowest recorded values in severely hydrated camels. Despite low morning body temperatures, camels sought shade to avoid evaporative water loss but after drinking, they spent more time in the sun. Water deprived camels are known to compensate the number of kilograms of body weight lost by drinking equivalent number of liters of water, and this has been assumed to indicate a full recovery. However, diminished food and salt intake, and sodium loss via urine and feces, are seldom considered. During dehydration, W16 camels increased plasma vasopressin levels, which decreased upon drinking, but aldosterone concentration increased to retain sodium and camels took more than two weeks to recover. Camels maintained milk production during 8 days of water deprivation, to improve milk production, more frequent watering is recommended in the dry season.